Respirable Dust Levels, Years of Service, and Pulmonary Physiological Disorders in Marble Home Industry Workers - Alia, Siti Arum; Widajati, Noeroel; Martiana, Tri; Sari, Firda Qurba; Tualeka, Abdul Rohim (Folia Medica Indonesiana, 2022)
Highlights: • The strength of the relationship between respiratory dust levels and pulmonary function disorders could not be obtained. • The weakness level of correlation between years of service and pulmonary function disorders. Abstract: Environmental dust in the workplace exposes the workers as they are breathing. The dust is inhaled into the respiratory tract and causes occupational diseases in the form of pulmonary function disorders. Workers in the marble industry are also prone to dust exposure. This study aimed to analyze the correlation between years of service, respiratory dust levels, and pulmonary function disorders in marble home industry workers in Tulungagung Regency, Indonesia. This study was a descriptive observational study with data from a cross-sectional technique. The population was 18 workers taken as respondents. The independent variables in this study were years of service and the level of respirable dust, while the dependent variable was the pulmonary function disorders experienced by the workers. The data were analyzed using the Correlation Contingency test. There was a close correlation between years of service and pulmonary function disorders by 0.196, indicating that the relationship between those variables was weak. The strength of the relationship between respiratory dust levels and pulmonary function disorders could not be obtained because the constant results met the threshold value. The correlation between years of service and pulmonary function disorders was weak, and the relationship between respiratory dust level and pulmonary function disorders could not be obtained.